When teaching must go on: ESP teachers’ strategies and challenges during COVID-19 Pandemic - Luluk Iswati (Makassar State University, 2021)
Abstract. Online classes have been rampant since the global spread of COVID-19. ESP teaching in higher education institutions is no exception, following the national government’s call to employ an online mode of teaching. Although technology has been long used to facilitate the teaching-learning process, the practice of online teaching is not without problems. Thus, this study was aimed at investigating ESP teachers’ strategies to make effective lessons delivery, optimize students class participation, and what challenges were emergent during their online teaching. The participants of this study were six ESP teachers in five private and one state universities who teach in various non-English departments. Data were gathered through interviews via WhatsApp. The findings showed that the strategies employed by ESP teachers were among others: ensuring instruction clarity, employing various learning platforms, virtual grouping, using authentic materials, etc. To optimize students’ online class participation was done by scoring students’ active participation, not giving non-doable tasks, using more asynchronous than synchronous method, etc. The challenges are having inconsistent internet connection, teaching while taking care for children, difficulty in monitoring students’ progress, etc. The findings imply the need of serious attention from higher education institutions in conducting ESP online teaching during this pandemic as it requires not only technical preparedness, but also most importantly the human aspect involved in it. Keywords: strategies, challenges, online teaching, ESP, pandemic